2014
DOI: 10.3892/ijmm.2014.2046
|View full text |Cite
|
Sign up to set email alerts
|

The combination of ursolic acid and leucine potentiates the differentiation of C2C12 murine myoblasts through the mTOR signaling pathway

Abstract: Abstract. Aging causes phenotypic changes in skeletal muscle progenitor cells that lead to the progressive loss of myogenic differentiation and thus a decrease in muscle mass. The naturally occurring triterpene, ursolic acid, has been reported to be an effective agent for the prevention of muscle loss by suppressing degenerative muscular dystrophy. Leucine, a branched-chain amino acid, and its metabolite, β-hydroxy-β-methylbutyric acid, have been reported to enhance protein synthesis in skeletal muscle. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…However, our results do not exclude the possibility that there exist other signaling pathways mediating the effects of serine. Nevertheless, these results indicated that except for supporting cellular proliferation by providing one‐carbon units and other substrates through its catabolism, serine also activated the signaling pathway that promote proliferation, as other amino acids such as arginine and leucine did . Previous studies had reported several amino acid sensors such as arginine sensors (CASTOR and SLC38A9) and leucine sensor (Sestrin 2) for the mTOR pathway.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, our results do not exclude the possibility that there exist other signaling pathways mediating the effects of serine. Nevertheless, these results indicated that except for supporting cellular proliferation by providing one‐carbon units and other substrates through its catabolism, serine also activated the signaling pathway that promote proliferation, as other amino acids such as arginine and leucine did . Previous studies had reported several amino acid sensors such as arginine sensors (CASTOR and SLC38A9) and leucine sensor (Sestrin 2) for the mTOR pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, these results indicated that except for supporting cellular proliferation by providing one-carbon units and other substrates through its catabolism, serine also activated the signaling pathway that promote proliferation, as other amino acids such as arginine and leucine did. 32,33 Previous studies had reported several amino acid sensors such as arginine sensors (CASTOR and SLC38A9) 34,35 and leucine sensor (Sestrin 2) 36 for the mTOR pathway. Consequently, future study is needed to explore serine sensors and elucidate the mechanism by which the mTOR pathway detects and transmits the serine signal.…”
Section: Discussionmentioning
confidence: 99%
“…25 Several materials, such as leucine and ursolic acid, as well as exercise, have been known to induce skeletal muscle hypertrophy stimulating v-akt murine thymoma viral oncogene homolog (Akt) or mammalian target of rapamycin (mTOR) signaling. [26][27][28][29][30][31][32] Activation of mTOR generates upregulation of phosphorylated eukaryotic translation initiation factor 4E-binding protein 1 (p-4E-BP1) or phosphorylated 70 kDa ribosomal protein S6 kinase (p-P70S6K). Those signals induce hypertrophy by enhancing translation of mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous studies, many kinds of materials, such as ursolic acid and leucine, 26,32,37,51 as well as exercise that have been known to induce skeletal muscle hypertrophy are associated with mTOR and transforming growth factorbeta signaling. 21,26,27 SF also activated signaling pathway of mTOR/p-P70S6K and p-4E-BP1 in early phases of differentiation (Figure 2).…”
mentioning
confidence: 99%
“…25 Several materials, such as leucine and ursolic acid, as well as exercise, have been known to induce skeletal muscle hypertrophy stimulating v-akt murine thymoma viral oncogene homolog (Akt) or mammalian target of rapamycin (mTOR) signaling. [26][27][28][29][30][31][32] Activation of mTOR generates upregulation of phosphorylated eukaryotic translation initiation factor 4E-binding protein 1 (p-4E-BP1) or phosphorylated 70 kDa correspondence: cheol Min Kim center for anti-aging Industry, Pusan National University, 70-16, eomgung-ro, sasang-gu, Busan 47046, republic of Korea Tel +82 51 315 7416 Fax +82 51 583 8820 email kimcm@pusan.ac.kr ribosomal protein S6 kinase (p-P70S6K). Those signals induce hypertrophy by enhancing translation of mRNAs.…”
Section: Introductionmentioning
confidence: 99%